Responses of white yam (Dioscorea rotundata) cultivars to inoculation with three viruses - Odu, B.O.; Hughes, J.D.A.; Asiedu, Robert; Ng, N.Q.; Shoyinka, S.A.; Oladiran, O.A. (Wiley, 2004)
The responses of 24 white yam (Dioscorea rotundata) cultivars to mechanical and vector transmission with each of three viruses infecting yams were assessed through enzyme-linked immunosorbent assay (ELISA) and symptom development. The viruses were Dioscorea alata virus (DAV), genus Potyvirus; Dioscorea alata bacilliform virus (DaBV), genus Badnavirus; and Cucumber mosaic virus (CMV), genus Cucumovirus. Only TDr 95-128, a landrace cultivar from Nigeria, developed symptoms of infection with CMV and DaBV following mechanical and vector transmission, respectively. PAS-ELISA showed that nine genotypes remained uninfected by DAV and 11 were uninfected by CMV or DaBV. Genotypes TDr 747 and TDr 1640 both showed resistance to all three viruses.